Penerapan Model Pembelajaran SM2CL untuk Meningkatkan Keterampilan Berpikir Kritis Kreatif dan Minat Belajar Biologi Siswa - Injilia Tewal; Fanny Nella Nanlohy; Nonny Manampiring (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The goal to be achieved from this study is to Improve Critical and Creative Thinking Skills, as well as Increase Students' Interest in Learning Biology in Class XI A4 SMA Negeri 1 Airmadidi Through the Application of the Synectics, Mind Maps, Cooperative Learning (SM2CL) Learning Model. The problems in this study are low interest in learning students; Students are more likely to be passive when studying; Teachers have never used learning models that can make students think critically and creatively; Learning is more teacher-centered. The research method used is the Classroom Action Research (PTK) method. The results of the research conducted in class XI A4 of SMA Negeri 1 Airmadidi showed that the acquisition of scores in the first cycle with a classical completion percentage of 38.88% increased to 66.66% in the second cycle. Although the classical completeness did not reach 75%, individually. Namely, 24 out of 36 students got a satisfactory score above the KKM, the highest score of 95, and the lowest score of 85 in cycle II. The score obtained from the learning interest questionnaire in the first cycle was at the percentage of 68% to 70% in the second cycle, and both were in a good category. Then, subject teachers and the school need to consider and evaluate some things, namely, the character of 12 students who did not want to do assignments at all from cycle I to cycle II.